AYURVEDIC MANAGEMENT OF RHEUMATIC FEVER: A SUCCESSFUL CASE REPORT - Ratnam Thekkayil, *Sanand; Patil, Vasant; Moosa Koya, Mabin; Ratnam, Iglhyza (International Journal of Ayurveda and Pharma Research, 2018)
Rheumatic fever is a rare but potentially life-threatening disease that may occur as complication of untreated infection caused by bacteria called group Astreptococcus. The main clinical features are -fever, myalgia, swollen and painful joints, and in some cases, a red, grille like rash typically manifest two to four weeks after a bout of streptococcal infection. In some cases, though, the infection might be too mild to recognize clinically. A 27year old male case was admitted in SSANH on 27/5/2015 with following chief complaints - severe pain and stiffness over multiple joints symmetrically since 2years, swelling of larger joints of both upper and lower limbs symmetrically since 2 years and recurrent episodes of fever accompanied with dyspnoea and body pain. The case was diagnosed as Rheumatic fever and treated with Rasnasapthakamkashayam, Rasasindhooram, Yogarajaguggulu as main internal medications and treatments like choornakizhi, Choornavasthi and Lavana Kizhi. The Ayurvedic management provided better relief in subjective and as well as objective parameters.